Going off scripts: emotional labor and technoliberal managerialism. Issue 2 (15th March 2022) - Salzano, Matthew; Yang, Misti
ABSTRACT: Originally conceived to highlight problematic labor relations that required emotions, the term emotional labor is now deployed to describe emotional relations that require problematic labor. In this paper, we identify how digital platforms have amplified this inverted form of emotional labor and spawned a phenomenon we term technoliberal managerialism, or the use of the connection, quantification, control, tracking, and optimization capacities of technology to manage everyday interactions. Through the analysis of viral self-help Twitter threads, a mobile application, and an algorithmic prototype we trace how the resulting habituation rewards happiness, efficiency, and uniformity at the expense of moodiness, messiness, and difference. Ultimately, we argue that going off scripts and embracing the "fuck up" can help resist technoliberalism.